2003
DOI: 10.1089/104454703322650176
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Low-Level Laser for Control of Painful Stomatitis in Patients with Hand-Foot-and-Mouth Disease

Abstract: LLLT is a useful method to control HFMD stomatitis by shortening the painful period, with its high acceptability and lack of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Toida et al. (47) found that low‐level laser therapy effectively shortened painful periods when it was used to control symptoms of stomatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toida et al. (47) found that low‐level laser therapy effectively shortened painful periods when it was used to control symptoms of stomatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Colvard & Kuo (18) showed that CO 2 laser treatment relieved pain on application of laser energy, while Convissar & Massoumi-Sourey (23) found the same results when using Nd:YAG lasers. Toida et al (47) found that low-level laser therapy effectively shortened painful periods when it was used to control symptoms of stomatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no general agreement about the exact way that LLLT may modulate wound healing. However, it has already been shown that LLLT can reduce pain, [5][6][7][8] and affect all three basic phases (i.e., inflammation, proliferation, and maturation) of wound healing. [9][10][11] In addition, positive LLLT effects have been observed in terms of increased wound tensile strength (TS), 12,13 and/or improved microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…Also light radiation at 829 nm is close to the 810 nm that was proved to be effective for bacteria's growth rate. In particular, the low-level laser at 830 nm has produced the effects in control of the painful stomatitis in patients with hand-foot (Toida et al 2003).…”
Section: Resultsmentioning
confidence: 99%